Uptake of workplace HIV counselling and testing: a cluster-randomised trial in Zimbabwe. - Elizabeth L Corbett; Ethel Dauya; Ronnie Matambo; Yin Bun Cheung; Beauty Makamure; Mary T Bassett; Steven Chandiwana; Shungu Munyati; Peter R Mason; Anthony E Butterworth; Peter Godfrey-Faussett; Richard J Hayes (PLoS Medicine)
Background HIV counselling and testing is a key component of both HIV care and HIV prevention, but uptake is currently low. We investigated the impact of rapid HIV testing at the workplace on uptake of voluntary counselling and testing (VCT). Methods and findings The study was a cluster-randomised trial of two VCT strategies, with business occupational health clinics as the unit of randomisation. VCT was directly offered to all employees, followed by 2 y of open access to VCT and basic HIV care. Businesses were randomised to either on-site rapid HIV testing at their occupational clinic (11 businesses) or to vouchers for off-site VCT at a chain of free-standing centres also using rapid tests (11 businesses). Baseline anonymised HIV serology was requested from all employees. HIV prevalence was 19.8% and 18.4%, respectively, at businesses randomised to on-site and off-site VCT. In total, 1,957 of 3,950 employees at clinics randomised to on-site testing had VCT (mean uptake by site 51.1%) compared to 586 of 3,532 employees taking vouchers at clinics randomised to off-site testing (mean uptake by site 19.2%). The risk ratio for on-site VCT compared to voucher uptake was 2.8 (95% confidence interval 1.8 to 3.8) after adjustment for potential confounders. Only 125 employees (mean uptake by site 4.3%) reported using their voucher, so that the true adjusted risk ratio for on-site compared to off-site VCT may have been as high as 12.5 (95% confidence interval 8.2 to 16.8). Conclusions High-impact VCT strategies are urgently needed to maximise HIV prevention and access to care in Africa. VCT at the workplace offers the potential for high uptake when offered on-site and linked to basic HIV care. Convenience and accessibility appear to have critical roles in the acceptability of community-based VCT.